1996
DOI: 10.1074/jbc.271.31.18939
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Xenopus laevis Mitochondrial Single-stranded DNA-binding Protein on Primer-Template Binding and 3′→5′ Exonuclease Activity of DNA Polymerase γ

Abstract: Mitochondrial DNA (mtDNA) is replicated by DNA polymerase ␥ by a strand displacement mechanism involving mitochondrial single-stranded DNA-binding protein (mtSSB). mtSSB stimulates the overall rate of DNA synthesis on singly-primed M13 DNA mainly by stimulating the processivity of DNA synthesis rather than by stimulating primer recognition. We used electrophoretic mobility shift methods to study the effects of mtSSB on primer-template recognition by DNA pol ␥. Preliminary experiments showed that single mtSSB t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…We have previously shown that authentic Xenopus DNA pol ␥ binds to oligonucleotide substrates and retains polymerase activity following native gel electrophoresis (23). Binding of the human catalytic subunit alone produced a shifted complex with a more rapid gel mobility than that observed for the Xenopus pol ␥ holoenzyme (compare lanes 2 and 3 in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that authentic Xenopus DNA pol ␥ binds to oligonucleotide substrates and retains polymerase activity following native gel electrophoresis (23). Binding of the human catalytic subunit alone produced a shifted complex with a more rapid gel mobility than that observed for the Xenopus pol ␥ holoenzyme (compare lanes 2 and 3 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The homopolymeric template was included in this analysis since we have previously shown that this is a preferred template for DNA pol ␥ because it does not present the enzyme with blocks to replication that require a mitochondrial single-stranded DNA binding protein (SSB) as an additional processivity factor (23). In each case, the primers were 32 P end labeled for the primer extension assays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The preparation from Roche Molecular Biochemicals was selected for repair assays. DNA pol ␥ was purified from an Xenopus laevis ovary homogenate as described (19,20). The preparation used in this study had a specific activity of 30 units/ml where 1 unit corresponds to incorporation of 1 nmol of TMP on a poly(dA)-oligo(dT) template-primer in 60 min at 30°C.…”
Section: Abasic (Ap)mentioning
confidence: 99%